Den norske avdeling av Grundtvig-Selskabet af 8. september 1947: Årsrapport 2006-2007 - Heggem, Synnøve Sakura (Grundtvig-Studier, 2007)
Report on the Grundtvig Society’s company from the norwedian department By Synnøve Sakura Heggem